Ministry of Trade and Industry Decree No. 31 of the Year 2021 Amending Article (22) of the Statute of Rules Enforcing the Provisions of the Law on Import and Export = وزارة التجارة والصناعة قرار رقم 31 لسنة 2021 بتعديل المادة (22) من لائحة القواعد المنفذة لأحكام قانون الاستيراد والتصدير - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic